2018
DOI: 10.1002/vjch.201800026
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolites from the marine‐derived fungus Paraconiothyrium sp. VK‐13

Abstract: Chemical investigation of a fermentation culture of the marine endophytic fungus Paraconiothyrium sp. VK‐13 resulted in the isolation of five compounds, including a new phenolic compound, 1‐(2,5‐dihydroxyphenyl)‐1‐oxobutan‐3‐yl acetate (1) and four known metabolites, 1‐(2,5‐dihydroxyphenyl)‐2‐buten‐1‐one (2), 3,7‐dimethyl‐1,8‐dihydroxy‐6‐methoxyisochroman (3), modiolides A (4) and B (5). Their chemical structures were identified based on 1D, 2D NMR, and MS spectroscopic analysis and comparison with the data re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…(3), 3-chloro-2,5dihydroxybenzyl alcohol (4), and phydroxybenzaldehyde (5). It is noted that this is the first time to report the in vitro anti-inflammatory effects of compounds 1, 3, and 4.…”
Section: Anti-inflammatory Assaymentioning
confidence: 95%
See 1 more Smart Citation
“…(3), 3-chloro-2,5dihydroxybenzyl alcohol (4), and phydroxybenzaldehyde (5). It is noted that this is the first time to report the in vitro anti-inflammatory effects of compounds 1, 3, and 4.…”
Section: Anti-inflammatory Assaymentioning
confidence: 95%
“…mairei has been reported to produce the anticancer drug taxol. [3] In our continuing search for secondary metabolites from the Vietnamese marine-derived fungi, [4,5] we found that an EtOAc extract of the fungal strain Aspergillus sp. IMBC-FP2.05 displays NO inhibitory effects in LPS-stimulated RAW264.7 cells.…”
Section: Introductionmentioning
confidence: 99%
“…PSU-F22, 81 Paraconiothyrium sp. VK-13, 6,92 and Microsphaeropsis arundinis . 93 Cephalosporolide C was found in extracts obtained from cultures of closely related Cephalosporium aphidicola ACC 3490, 94 Cordyceps militaris BCC 2816, 95 and Isaria fumosorosea ACCC 37775.…”
Section: Analysis Of Ten-membered Lactones Described For the Entire P...mentioning
confidence: 98%
“…[7] However, chemical profile of the Xenomyrothecium genus has yet to be discovered so far. In our continuing search for secondary metabolites from the Vietnamese marinederived fungi, [8,9] we conducted a chemical investigation of a fungal strain Xenomyrothecium sp. IMBC-FP2.11 isolated from an unidentified sponge.…”
Section: Introductionmentioning
confidence: 99%